Evaluation of dynamic simulation model for wheat genotypes under diverse environments in India - ATTRI, S. D.; SINGH, K. K.; KAUSHIK, ANUBHA; RATHORE, L. S.; MENDIRATTA, NISHA; LAL, B. (MAUSAM, 2001)
Performance of dynamic crop growth simulation model (CERES -Wheat v3.5) has been evaluated for various wheat genotypes in wheat growing regions of India. The genetic coefficients were developed and sensitivity analysis was carried out for the genotypes under study. The simulated phenology and yield were found in agreement with observed ones suggesting that calibrated model may be operationally used with routinely observed soil, crop and weather parameters.